2011
DOI: 10.1016/j.exger.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

dSir2 and longevity in Drosophila

Abstract: The silent information regulator 2 (Sir2 or Sirtuin) family of proteins is highly conserved and has been implicated in the extension of longevity for several species. Mammalian Sirtuins have been shown to affect various aspects of physiology including metabolism, the stress response, cell survival, replicative senescence, inflammation, the circadian rhythm, neurodegeneration, and even cancer. Evidence in Drosophila implicates Sir2 in at least some of the beneficial effects of caloric restriction (CR). CR delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 69 publications
1
27
0
3
Order By: Relevance
“…Studies in mice and humans have shown that resveratrol can lower glucose levels and may be an effective intervention for the treatment of type 2 diabetes, a disease that is prevalent in both aging and obesity Milne et al 2007;Szkudelska and Szkudelski 2010). Resveratrol has also been shown to reduce oxidative damage in human cells and animal models (Szkudelska and Szkudelski 2010;Baur 2010;Frankel et al 2011). These studies along with the current findings support the hypothesis that resveratrol can promote health span partly through modulating oxidative stress pathways.…”
Section: Discussionsupporting
confidence: 82%
“…Studies in mice and humans have shown that resveratrol can lower glucose levels and may be an effective intervention for the treatment of type 2 diabetes, a disease that is prevalent in both aging and obesity Milne et al 2007;Szkudelska and Szkudelski 2010). Resveratrol has also been shown to reduce oxidative damage in human cells and animal models (Szkudelska and Szkudelski 2010;Baur 2010;Frankel et al 2011). These studies along with the current findings support the hypothesis that resveratrol can promote health span partly through modulating oxidative stress pathways.…”
Section: Discussionsupporting
confidence: 82%
“…Knocking out dSir2 shortens lifespan 20 . Lifespan extension upon dSir2 overexpression has been found in a number of different configurations, including several different transgenes, different drivers, tissue-specific and adult-only inductions 21 . However, several of these have also been challenged recently 18 .…”
Section: Sirtuins In Simple Model Organismsmentioning
confidence: 99%
“…Since Sir2 promotes longevity as overexpression of SIR2 gene reproducibly extends lifespan in yeast, does activated Sir2 contribute to the longevity effect of CR? Interestingly, although sirtuin's role in CR has been challenged in yeast and worms, the evidence for Sir2 being critical for CR in flies seem plentiful 21 . In mammals, although direct genetic tests remain difficult, accumulating evidence suggest that sirtuins are regulated in various tissues at both expression levels and metabolic states.…”
Section: Controversy 1: Sirtuins Mediates Effects Of Calorie Restrictionmentioning
confidence: 99%
“…Згідно з літературними даними, гени Sir регулюють процеси старіння, транскрипції, апоптозу, запалення [18,19]. У дослідженнях на клітинах дріжджів встановлено, що сір-туіни можуть не тільки змінювати щільність гістонової упаковки і таким чином регулюва-ти активність генів, а й брати участь у репара-ції пошкодженої ДНК [20,21].…”
Section: результати та їх обговоренняunclassified
“…У дослідженнях на клітинах дріжджів встановлено, що сір-туіни можуть не тільки змінювати щільність гістонової упаковки і таким чином регулюва-ти активність генів, а й брати участь у репара-ції пошкодженої ДНК [20,21]. Встановлено, що сіртуіни відіграють важливу роль у регу-ляції тривалості життя та розвитку нейроде-генеративних захворювань дрозофіл [18,19,21]. Показано, що збільшення експресії Sir2 втричі у жировій тканині дрозофіл збільшує тривалість життя як самців, так і самиць на 13 % [22].…”
Section: результати та їх обговоренняunclassified